Yogyakarta Modernity Dynamics: A Study of Code-Switching in Kedaulatan Rakyat’s Weekly Short Stories from 2010 to 2015 - Fransisca, Kristanti (Journal of Language and Literature, 2017)
This research analyzes how language reflects Yogyakarta modernity dynamics through the analysis of Kedaulatan Rakyat’s weekly short stories from 2010 to 2015. The research is aimed to find out how the city’s modernity is portrayed through language by the means of code-switching in the weekly short stories. It identifies the phenomena of code-switching in the short stories and analyzes whether or not the switch is an illustration of the city’s modernity through language. Keywords: code-switch, short stories, modernity, Yogyakarta.